Accuracy of closed pleural biopsy in the diagnosis of malignant pleural effusion - Renata Báez-Saldaña; Uriel Rumbo-Nava; Araceli Escobar-Rojas; Patricia Castillo-González; Santiago León-Dueñas; Teresa Aguirre-Pérez; María Eugenia Vázquez-Manríquez (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: Previous studies have demonstrated that closed pleural biopsy (CPB) has a sensitivity of less than 60% for diagnosing malignancy. Therefore, controversy has recently emerged regarding the value of CPB as a diagnostic test. Our objective was to assess the accuracy of CPB in diagnosing malignancy in patients with pleural effusion. Methods: This was a prospective 8-year study of individuals who underwent CPB to establish the etiology of pleural effusion. Information on each patient was obtained from anatomopathological reports and medical records. When CPB findings showed malignancy or tuberculosis, the biopsy was considered diagnostic, and that was the definitive diagnosis. In cases in which biopsy histopathological findings were nonspecific, a definitive diagnosis was established on the basis of other diagnostic procedures, such as thoracoscopy, thoracotomy, fiberoptic bronchoscopy, biochemical and cellular measurements in pleural fluid, and/or microbiological tests. The accuracy of CPB was determined with 2 × 2 contingency tables. Results: A total of 1034 biopsies from patients with pleural effusion were studied. Of those, 171 (16.54%) were excluded from the accuracy analysis either because of inadequate samples or insufficient information. The results of the accuracy analysis were as follows: sensitivity, 77%; specificity, 98%; positive predictive value, 99%; negative predictive value, 66%; positive likelihood ratio, 38.5; negative likelihood ratio, 0.23; pre-test probability, 2.13; and post-test probability, 82. Conclusions: CPB is useful in clinical practice as a diagnostic test, because there is an important change from pre-test to post-test probability.